2016
DOI: 10.1093/ijpor/edw003
|View full text |Cite
|
Sign up to set email alerts
|

Selective Exposure, Political Polarization, and Possible Mediators: Evidence From the Netherlands

Abstract: One of the main lines of reasoning in the contemporary debate on media effects is the notion that selective exposure to congruent information can lead to political polarization.Comparatively little experimental evidence, however, is available to empirically back up the claim of a causal relationship. Even less is known about the mechanisms behind such an effect. We conducted an online experiment with a sample matching the characteristics of the Dutch population closely (N = 501), and investigate how selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
(29 reference statements)
1
25
0
6
Order By: Relevance
“…Beyond specific issues, the relevance, surprising or controversial nature of the news affect how viral it goes (Rudat;Buder;Hesse, 2014). Trilling et al (2016) found that news within a framework of conflict was shared 11% more on Twitter, and 9% more on Facebook. Other factors that have similar effects are the human interest (García-Perdomo et al, 2007) or the emotional component of the news (Berger;Milkman, 2010;Kim, 2015), especially that with positive or comforting content (Berger;Milkman, 2010;Bakshy et al, 2012).…”
Section: 'News Sharing': Dismantling the 'Gatekeeper'mentioning
confidence: 99%
“…Beyond specific issues, the relevance, surprising or controversial nature of the news affect how viral it goes (Rudat;Buder;Hesse, 2014). Trilling et al (2016) found that news within a framework of conflict was shared 11% more on Twitter, and 9% more on Facebook. Other factors that have similar effects are the human interest (García-Perdomo et al, 2007) or the emotional component of the news (Berger;Milkman, 2010;Kim, 2015), especially that with positive or comforting content (Berger;Milkman, 2010;Bakshy et al, 2012).…”
Section: 'News Sharing': Dismantling the 'Gatekeeper'mentioning
confidence: 99%
“…Hence, people are provided with the opportunity to select a media diet that matches their immigration attitudes, which is not necessarily the case for all political issues. It should also be noted that findings from selective exposure literature suggest that people are likely to select media content that matches their immigration attitudes (Trilling, van Klingeren, & Tsfati, 2017).…”
Section: Clarifying the Causal Chain By Testing The Reinforcing Spiramentioning
confidence: 99%
“…Mainstreamdiskurses", die einen Ausgangspunkt für politische Aktion und Partizipation darstellen können (Fraser 1990 (Stroud 2017). Die These der selektiven Informationsauswahl wird prinzipiell durch einige Laborexperimente gestützt (Garrett et al 2014;Knobloch-Westerwick und Meng 2009;Iyengar und Hahn 2009;Trilling et al 2016), wobei sich die Nutzer bei ihrer Auswahl an diversen Merkmalen einer Nachricht (Nachrichtenquelle, Nachrichteninhalt oder Zuordnung zu einer bestimmten politischen Partei) zu orientieren scheinen (Knobloch-Westerwick und Meng 2009;Iyengar und Hahn 2009;Stroud 2010).…”
Section: Konzeptualisierung: Fragmentierung Und Polarisierungunclassified
“…So scheint die Stärke von Polarisierungseffekten beim Konsum konsonanter Informationen keinesfalls einheitlich zu sein und in einigen Fällen lässt sich eine gegensätzliche Wirkungsrichtung beobachten, so dass der Konsum dissonanter Informationen zu einer Reduktion von themenbasierter Polarisierung führt, identitätsbasierte Polarisierung allerdings zunimmt (Tucker et al 2018). Individuelle Merkmale wie die Stärke von Einstellungen, Ausprägung von Parteiidentitäten, Wichtigkeit von Themen oder der affektive Status des Rezipienten (insbesondere Wut) spielen eine entscheidende Rolle beim Auftreten von Polarisierungseffekten (Mason 2015;Trilling et al 2016;Wojcieszak et al 2018).…”
Section: Soziale Netzwerkseitenunclassified